Determinants that Influence Intention to Share Information on Blogs - Koh, Boon Siew (2011)
This study examines factors that influence the intention to share knowledge through blog among Intel's users. The study was a cross sectional study where respondents' perception was measured at one point in time. 118 respondents participated in this study. In this study, three factors were tested to understand the intention to share knowledge among bloggers at Intel. Correlation analyses were conducted to test the relationship between organizational factors, individual factors and technology factors and intention to share knowledge through blog, whereas descriptive analysis was conducted to analyze demographic characteristics of participants. To test which factor has the significant contribution towards intention to share knowledge through blog, regression analysis was conducted. The results show that there was an association between all the three factors (organizational, individual and technology) and intention to share knowledge through blog. Though all the three factors indicate significant positive relationship with intention to share information through blog, individual factor makes the strongest contribution to explain the intention to share knowledge through blog.